Assessment System for Testing the Evaluation of Diversity in Traditional Malay Dance by Early Childhood Students - Watini, Sri Watin; Aini, Qurotul; Khoirunisa, Alfiah; Rahardja, Untung (International Journal of Psychosocial Rehabilitation, 2020)
Malay culture is spread in several locations including the Malay Peninsula, Kalimantan, West Kalimantan, Sumatra, Thailand, Burma, Singapore, Sarawak, Sabah, and other small islands. Malay is one of the Austronesian ethnic groups and, to this day, Malay preserves Austronesian heritage. As one way to develop a culture that is owned by developing in the world of technology, given the current development of technology in all aspects is very significant. However, at this time, the development of the preservation of cultural arts has not been touched on technology, which evaluates early childhood dance evaluations which are still carried out in paper media. Of course this is considered less efficient because it still uses conventional methods that can cause the sheet to be tucked or lost. From the subject matter, it is necessary to improve the assessment of examiners so that they can be accessed online on the Taekwondo belt UKT to be more structured, directed, effective and far more efficient and can be accessed online. In the development of the examiner’s assessment system using the YII Framework. Keywords: Traditional Dances, Malay Culture, Examiner Assessment, YII Framework Malay culture is spread in several locations including the Malay Peninsula, Kalimantan, West Kalimantan, Sumatra, Thailand, Burma, Singapore, Sarawak, Sabah, and other small islands. Malay is one of the Austronesian ethnic groups and, to this day, Malay preserves Austronesian heritage. As one way to develop a culture that is owned by developing in the world of technology, given the current development of technology in all aspects is very significant. However, at this time, the development of the preservation of cultural arts has not been touched on technology, which evaluates early childhood dance evaluations which are still carried out in paper media. Of course this is considered less efficient because it still uses conventional methods that can cause the sheet to be tucked or lost. From the subject matter, it is necessary to improve the assessment of examiners so that they can be accessed online on the Taekwondo belt UKT to be more structured, directed, effective and far more efficient and can be accessed online. In the development of the examiner’s assessment system using the YII Framework.